2018
DOI: 10.1177/8756972818803482
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Improved Understanding of Agile Project Governance

Abstract: The purpose of this study is to provide understanding of project governance practices in agile projects. A systematic review of the previous agile literature is conducted to identify and categorize agile project governance practices, which are synthesized in a six-dimensional framework. The study contributes to the literature by contrasting traditional and agile project governance practices and by identifying new practices emerging in agile projects, while also noting remaining gaps in knowledge. The implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 93 publications
(258 reference statements)
0
68
0
6
Order By: Relevance
“…In investigating how governance can improve decision-making in groups, we looked at three issues. Lappi et al (2018) show how governance can improve the inputs and processes of a team working framework, (Reader et al, 2009). Similarly, Müller et al (2015) invoke institutional theory to show that governance can improve team working.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In investigating how governance can improve decision-making in groups, we looked at three issues. Lappi et al (2018) show how governance can improve the inputs and processes of a team working framework, (Reader et al, 2009). Similarly, Müller et al (2015) invoke institutional theory to show that governance can improve team working.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Müller et al (2016b) say that the governance of the temporary organization should allow flexibility to cope with risk and the uniqueness of the project. Lappi et al (2018) say flexibility is important for agile projects and aids the connection of the projects to corporate strategy. Riis et al (2019) show how organizations get value from multiple small projects by establishing and maturing links between the levels.…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Too and Weaver [19] examined existing project governance research and proposed that good project governance should achieve optimal balance between portfolio management, project sponsorship, project management and office and program support and improve project performance. Lappi et al [20] reported a six-dimensional framework of project governance in agile projects. Derakhshan et al [21] developed a project governance model adopting a stakeholder approach.…”
Section: Introductionmentioning
confidence: 99%